Sistem Pendukung Keputusan Dalam Penggunaan Pestisida Untuk Tanaman Dataran Rendah - Herasmus, Hilda (Riset Sinergi Indonesia (RISINDO), 2022)
A good decision support system for the use of pesticides, namely by selecting pesticides that are in accordance with the Plant Destruction Orgasm (OPT) and the dosage for pesticide application. In addition, the Decision Support System is also useful for choosing various decision alternatives that result from processing the information obtained on a number of alternatives that may be proposed to decision makers to determine the best of several good choices. The purpose of this study is to provide an alternative decision support system in the use of good pesticides using the Analytical Hierarchy Process (AHP) method, so that the results of calculations carried out with the AHP method can assist farmers in using pesticides for lowland vegetables and the resulting or transaction value. carried out by farmers can be entered directly into the database.